Static compensators assessment in the wind power systems transient stability with induction generators in distribution networks (2014)
ABSTRACT: Currently, most wind power plants use induction generators in their operation. Due to their nature, these generators are usually equipped either with static or dynamic compensation devices. This paper presents an assessment of the use of static compensators in the stability of wind induction generators. To perform the study, a base case was used in which a three-phase fault that destabilizes the network is simulated. Then, to stabilize the network and avoid an eventual disconnection or damage of the wind power farm, three compensation alternatives were considered: capacitors, STATCOM and SVC. The effectiveness and performance of each of these alternatives were evaluated. Simulations were carried out in Simulink of MATLAB@, showing satisfactory results for the compensation alternatives under study. The performed simulations identified the STATCOM with IGBT as the most effective compensation under eventual contingencies. On the other hand, it was found that all the studied alternatives are equally effective for voltage compensation in steady state conditions.